Distribuição espacial de Tenuipalpus heveae Baker (Acari: Tenuipalpidae) na cultura da seringueira - Martins, Gustavo L. M. [UNESP]; Vieira, Marineide R. [UNESP]; Barbosa, José C. [UNESP]; Dini, Thiago A. [UNESP]; Manzano, Anderson M. [UNESP]; Alves, Bruno M. S. [UNESP]; Silva, Rodolfo M. [UNESP] (Sociedade Entomológica do Brasil, 2010)
The objective of this work was to study the spatial distribution of Tenuipalpus heveae Baker in rubber tree plantations. The experimental area was located in Marinópolis, State of São Paulo, and corresponded to a total of 1,000 plants (clone RRIM 600) divided in 100 plots of ten plants each. A total of 16 samplings were conducted, approximately once every 10 days, between December 2007 and June 2008. on each date, samples were taken from two plants per plot, each sample corresponding to the top 30 cm of a branch randomly taken from the median region of the canopy of each plant. The number of T. heveae was evaluated on three leaflets randomly taken from each sample, using a 20x power pocket magnifying glass. The number of mites was evaluated in two areas of 1 cm² delimited on the lower surface of each leaflet, being one along the midrib and the other along a lateral vein. The calculated dispersion indexes were: variance/mean relationship (I), index of Morisita (I´), coefficient of Green (Cx) and k exponent of negative binomial distribution. Tenuipalpus heveae showed aggregate distribution. The negative binomial distribution model was the most appropriate to represent the spatial distribution of the mite in the rubber tree plantation.
Spatial distribution of Tenuipalpus heveae Baker (Acari: Tenuipalpidae) on rubber tree plantations
Keywords: Hevea brasiliensis; Mite; sampling; Negative binomial distribution